1986
DOI: 10.3109/10641968609046609
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Neurofibromatosis Associated Renal Artery Stenosis with Hypertension by Percutaneous Transluminal Angioplasty

Abstract: A 12 year old girl with severe arterial hypertension was found to have neurofibromatosis associated bilateral stenoses of the main renal arteries and elevated plasma renin activity in the right main renal vein. Antihypertensive treatment was unable to normalize blood pressure. PTA of the right renal artery from a left axillary approach resulted in normalization of blood pressure and peripheral plasma renin activity. PTA seems to be an effective and safe method for treatment even of complicated forms of renal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
1

Year Published

1997
1997
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 12 publications
1
11
1
Order By: Relevance
“…Although 1 out of 3 cases with NF was "failed" as initial technical and clinical result, all cases were "improved" in follow up period. So we agree with other studies (14,15,26) that PTRA should be a treatment of choice in NF 1 patients.…”
Section: Discussionsupporting
confidence: 95%
See 2 more Smart Citations
“…Although 1 out of 3 cases with NF was "failed" as initial technical and clinical result, all cases were "improved" in follow up period. So we agree with other studies (14,15,26) that PTRA should be a treatment of choice in NF 1 patients.…”
Section: Discussionsupporting
confidence: 95%
“…Review of the literature, reveals slightly better results for PTRA in FMD and in TA (17,(21)(22)(23), whereas the results for renal artery stenosis due to NF are rather disappointing (24,25). But CASALINI et al (15) and MALLMAN et al (26) revealed that PTRA should be a treatment of choice also in NF patients. FOSSALI et al (14) also reported that surgical revascularization could be performed in more complex cases in which PTRA fails or complications occur.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The nature of the vascular involvement in neurofibromatosis has tended to prompt suggestions that surgery is unlikely to resolve the problem, especially as the lesions may be diffuse. Angioplasty was of benefit in temporarily resolving the aortic stenosis but unlike previous reports6 the stenosis recurred.…”
Section: Discussioncontrasting
confidence: 67%
“…8,13,[16][17][18]24,[37][38][39][40][41][42][43][44][45][46][47][48][49][50][51] In patients with peripheral arterial stenoses, vascular intervention may be indicated to ameliorate claudication 11,12,[16][17][18]24,52,[54][55][56] or prevent critical limb ischemia and limb loss. In those with splanchnic artery stenoses vascular intervention may be mandatory to enable enhancement of bowel perfusion.…”
Section: Vascular Interventionmentioning
confidence: 99%